Making space to write 'care-fully': Engaged responses to the institutional politics of research writing. (April 2022) - Dufty-Jones, Rae; Gibson, Chris
As pressures around academic writing mount, human geographers have developed critical strategies to resist and rework the institutional politics of research writing. Overlooked, until now, is the role of pedagogy. We advance an engaged pedagogy of research writing and use this concept to propose three practical strategies: (1) understanding writing as social practice; (2) reimagining the temporalities of writing; and, (3) reimagining the spatialities of writing. We argue that an engaged pedagogical approach expands the possibilities of how human geographers can critically and practically respond to the institutional politics of research writing.